2021
DOI: 10.1016/j.jaccas.2021.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality Treatment Planning for Congenital Heart Disease

Abstract: Corresponding Author

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…cardiac surgery), preventive, micro-or nanorobotics, cardiosurgical neuroprosthetics based on bioMEMS and bioNEMS). Clinical 3D modelling must be integrated with the pre-operative care of patients with heart defects, and the demand for these services is growing rapidly [22,43].The use of VR in cardiac surgery is not just in one area and the benefits may be subject to synergistic effects. Further work is needed to fully demonstrate the clinical benefits and improved outcomes in post-cardiac surgery patients as a result of VR-based methods and/or tools.…”
Section: Discussionmentioning
confidence: 99%
“…cardiac surgery), preventive, micro-or nanorobotics, cardiosurgical neuroprosthetics based on bioMEMS and bioNEMS). Clinical 3D modelling must be integrated with the pre-operative care of patients with heart defects, and the demand for these services is growing rapidly [22,43].The use of VR in cardiac surgery is not just in one area and the benefits may be subject to synergistic effects. Further work is needed to fully demonstrate the clinical benefits and improved outcomes in post-cardiac surgery patients as a result of VR-based methods and/or tools.…”
Section: Discussionmentioning
confidence: 99%
“…42,43 Several studies investigated the value of VR and AR in surgical or interventional therapy planning. 44,45 Ong et al 46 reported that use of VR presurgical planning in complex CHD allowed interaction with intra-and extracardiac anatomy. The authors concluded that VR served as a valuable complement to traditional preoperative planning methods.…”
Section: Introductionmentioning
confidence: 99%